Self-reported HPV vaccination status and HPV vaccine hesitancy in a nationally representative sample of emerging adults in Croatia - Nemeth Blažić, Tatjana; Božičević, Ivana; Kosanović Ličina, Mirjana Lana; Štulhofer, Aleksandar; Nola, Iskra Alexandra (Frontiers in Public Health, 2023)
The aim of this study was to determine self-reported human papillomavirus (HPV) vaccination status among emerging adults in Croatia, intention to get the HPV vaccine among unvaccinated and correlates of HPV vaccine hesitancy.Methods: Data were collected via a cross-sectional survey based on a probabilistic national sample.The sample included 1197 persons aged 18-25 years (50.6% were women) who were recruited from November 2021 to February 2022 as part of the commercial online panel. Analyses included 981 participants who correctly answered two "attention trap" questions using descriptive statistics and multivariate analyses. The data were post-hoc weighted for gender and age and adjusted for clustering effect. To adjust standard errors for the sampling design, multivariate analyses were carried out using the complex samples module in the IBM SPSS 27 statistical software package.Results: Overall, 18.3% of participants (25.0% of women and 11.7% of men) reported that they were HPV vaccinated while 21.9% did not know their HPV vaccination status. Of those vaccinated, 65.6% were women. The odds of being HPV vaccinated were significantly higher among female participants. Among unvaccinated, 35.4% expressed willingness to get the vaccine. The odds of vaccination hesitancy were significantly lower among women, participants who reported higher perceived risk of STIs and those who recognized that HPV could result in cervical cancer, and significantly higher among more religious individuals.Our findings suggest a need to increase HPV vaccination uptake in Croatia through raising awareness about HPV vaccine effectiveness but also through implementation of strategies to make vaccination more available.